Impact of Policies and Macroeconomic Variables on Tax Revenue and Effective Tax Rate of Infrastructure, Utility, and Transportation Sector Companies Listed in Indonesia Stock Exchange - Harahap, Mursal; Sinaga, Bonar M.; Manurung, Adler H.; Maulana, Tubagus Nur Ahmad (International Journal of Economics and Financial Issues, 2018)
Taxes are the major source of state revenue for financing government expenditures. Tax revenues are influenced by government policies and macroeconomic variables. This study aims to analyze the impact of macroeconomic and policy changes on tax revenue and effective tax rate (ETR). Panel data was utilized for companies in the infrastructure, utilities and transportation sector for the period 2010-2015. Analysis was carried out using a simultaneous equations model and estimated using the Two-Stage Least Squares (2SLS). Seidel’s method was selected to analyze the impact simulation. It was found that there was a greater inflationary impact on tax revenue and effective tax rate (ETR), causing them to increase, followed by tax rates, GDP, exchange rates and interest rates of the Bank of Indonesia (BI). Keywords: Effective Tax Rate, Macroeconomic variable, Policy Impact JEL Classification: EP5